2022
DOI: 10.1038/s41598-022-16332-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic exercise to improve motor function among children with Down Syndrome aged 0 to 3 years: a systematic literature review and meta‑analysis

Abstract: The effects and the prescription parameters of therapeutic exercise are not clear. For this reason, is needed to determine the effect of therapeutic exercises on the motor function of children with Down Syndrome (DS) aged 0 to 3 years. The present study is systematic review and meta-analysis of effectiveness outcomes in this population: gait, balance, motor development, fine motor skills, and executive functions. The databases of PubMed, PEDro, EMBASE, SCIELO, Lilacs, Cochrane library were searched from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Difficulties with FMS can impact their ability to perform self-care tasks, such as dressing and feeding themselves. Adapted PA can help children with DS to improve both GMS and FMS through specific activities that promote physical capacities, hand-eye coordination, finger dexterity, and hand strength, which are all movements that mechanically activate both hemispheres of the brain through the motor and sensory cortexes [21]. Exercise can stimulate the brain in such a way that neurons are often in a condition to handle different data from the outside environment, transforming them into the required task [22].…”
Section: Motor Skills In Pediatric Patients With Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties with FMS can impact their ability to perform self-care tasks, such as dressing and feeding themselves. Adapted PA can help children with DS to improve both GMS and FMS through specific activities that promote physical capacities, hand-eye coordination, finger dexterity, and hand strength, which are all movements that mechanically activate both hemispheres of the brain through the motor and sensory cortexes [21]. Exercise can stimulate the brain in such a way that neurons are often in a condition to handle different data from the outside environment, transforming them into the required task [22].…”
Section: Motor Skills In Pediatric Patients With Down Syndromementioning
confidence: 99%
“…Exercise can stimulate the brain in such a way that neurons are often in a condition to handle different data from the outside environment, transforming them into the required task [22]. In recent decades, research has shown that the proficiency in fundamental movement skills is important for promoting the physical (i.e., cardiorespiratory fitness, healthy weight) and psychosocial (i.e., physical self-concept) health of children [21].…”
Section: Motor Skills In Pediatric Patients With Down Syndromementioning
confidence: 99%
“…On the other hand, in children and adolescents with intellectual disabilities, improvements have been seen in health from resistance training [34] , [35] , in cardiorespiratory fitness from aerobic exercise [36] , and in body composition [37] , [38] . In addition, there are already reviews on the benefits of exercise in the population with DS, specifically in children and adolescents, where improvements in balance are mentioned [39] , in motor performance [40] , strength, and posture [41] . Also, improvements in health have been seen from exercise in adults with DS, specifically, improvements in cardiometabolic risk, muscle strength, and aerobic work capacity [42] , [43] , however, there are doubts regarding the intensity and frequency of its prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Their research points to a recognized necessity to tailor exercise therapy to better meet the needs of individuals with Down syndrome. This is particularly important when considering specific age groups, a focus evident in studies like those by Rodríguez-Grande et al (2022a and 2022b), which delve into therapeutic exercises for motor function improvement in young children and neuromuscular exercise research in this population (11,12). The emphasis on age-specific interventions illustrates the complexity and varying requirements across different age groups within the Down syndrome community.…”
Section: Introductionmentioning
confidence: 99%